2020
DOI: 10.1038/s41558-020-0705-4
|View full text |Cite
|
Sign up to set email alerts
|

Defining Southern Ocean fronts and their influence on biological and physical processes in a changing climate

Abstract: The Southern Ocean is a critical component of the global climate system and an important ecoregion that contains a diverse range of interdependent flora and fauna. The Southern Ocean also hosts numerous fronts: sharp boundaries between waters with different characteristics. As they strongly influence exchanges between the ocean, atmosphere and cryosphere, fronts are of fundamental importance to the climate system. However, rapid advances in physical oceanography over the past 20 years have challenged previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 94 publications
2
126
0
1
Order By: Relevance
“…However, this approach was challenged because these parameters are affected by the large-scale thermal expansion and steric sea-level rise occurring as a result of the warming of this circumpolar region. Recent studies found no significant long-term trend in either the annual mean latitude of zonal wind jets between 1979 and 2009 (Swart et al, 2015) or the zonally averaged latitude of ACC transport, which seem insensitive to changes in the SO's broad-scale structure (Gille, 2014;Chapman et al, 2020). The location of the ACC may be constrained by sea floor and land mass topography, particularly close to narrow gaps between land masses, such as Drake's Passage (high confidence; Moore et al, 1999).…”
Section: Currents and Eddiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach was challenged because these parameters are affected by the large-scale thermal expansion and steric sea-level rise occurring as a result of the warming of this circumpolar region. Recent studies found no significant long-term trend in either the annual mean latitude of zonal wind jets between 1979 and 2009 (Swart et al, 2015) or the zonally averaged latitude of ACC transport, which seem insensitive to changes in the SO's broad-scale structure (Gille, 2014;Chapman et al, 2020). The location of the ACC may be constrained by sea floor and land mass topography, particularly close to narrow gaps between land masses, such as Drake's Passage (high confidence; Moore et al, 1999).…”
Section: Currents and Eddiesmentioning
confidence: 99%
“…Ice shelf disintegration could have complex effects on upper ocean mixing and vertical carbon and nutrient fluxes depending on the relative forcing of increased exposure to winds and altered strength and position of the buoyant meltwater plume (e.g., Randall-Goodwin et al, 2015). Projected increases in eddy activity within the ACC and the anticipated changes in ocean currents and frontal positions will influence the transport and distribution of nutrients and carbon around the Southern Ocean, as well as air-sea exchange of CO 2 (Sallée et al, 2012;Rintoul, 2018;Chapman et al, 2020).…”
Section: Impact Of Climate-induced Physical Changes On Nutrient and Cmentioning
confidence: 99%
“…The solubility pump, whereby atmospheric CO 2 is taken up by dissolution into surface waters and subsequently subducted into the subsurface, exporting CO 2 into the ocean interior, is particularly strong in the high southern latitudes due to cold surface waters and deep and intermediate water mass formation (e.g., Sabine et al, 2004;Van Heuven et al, 2014;Gruber et al, 2019b). The Southern Ocean also has regions of strong upwelling linked to oceanographic fronts, which brings CO 2 -rich deep waters to the surface, increasing pCO 2 in surface waters, altering the carbonate system equilibrium and driving CO 2 release to the atmosphere (e.g., Pardo et al, 2017;Chapman et al, 2020). The biological pump is also important in the Southern Ocean, particularly during spring and summer (e.g., Ducklow et al, 2001;DeVries et al, 2012;Cavan et al, 2019a).…”
Section: Changes In the Southern Ocean Carbon Sinkmentioning
confidence: 99%
“…The Southern Ocean CO 2 sink has taken up approximately 40% of the total oceanic uptake of anthropogenic CO 2 (Orr et al, 2001;Fletcher et al, 2006;DeVries, 2014), increasing surface water pCO 2 and causing ocean acidification (Section "Ocean Acidification and Its Effects on the Ecosystem"). Export of CO 2 to the deep Southern Ocean occurs in specific locations and depends on the interactions between physical properties, such as mixed layer depth, ocean currents, fronts, eddies and winds, all of which are potentially sensitive to climate variability and change, and with bathymetric features (Sallee et al, 2012;Chapman et al, 2020). In addition to intense seasonality in sea-air CO 2 fluxes driven by the solubility and biological pumps, a high degree of interannual variability has been reported for particular regions, such as the WAP (Ito et al, 2018;Brown et al, 2019) and the Ross Sea (Dejong and Dunbar, 2017).…”
Section: Net Co 2 Sink Behaviour Of the Southern Oceanmentioning
confidence: 99%
“…Nel et al (2001) showed that once a GHA egg hatches, adult GHA breeding at Marion Island no longer travel to the STCZ and all foraging activity is restricted around prey aggregating mesoscale eddies in the lee of the ABFZ. As a result of climate change, southward shifts of the major frontal zones within the Southern Ocean has been predicted (Kim & Orsi, 2014;Wilson et al, 2016 but see Chapman et al, 2020;Meijers et al, 2012). Asdar (2018) recently showed that if there is a 1° latitudinal shift, either north or south, in the position of the PF, the PF will no longer interact with the ABFZ, producing fewer eddies.…”
Section: F I G U R Ementioning
confidence: 99%